Effect of alcohol on bone fragility - Štulić Miloš; Ćulafić Đorđe; Đonić Danijela (Medicinski Podmladak)
Excessive alcohol consumption is a risk factor for over 200 different diseases, including changes in bone remodeling. It is known that 30% of alcoholics who do not have liver cirrhosis have osteoporosis, and that 36% of them have radiologically proven pathological fractures of the spinal vertebrae. This publication presents an overview of modern literature on the mechanisms of alcohol's effects on bone, depending on the type and amount of alcohol. Various cellular and molecular mechanisms are considered responsible for the osteotoxicity of alcohol, including a direct effect on osteoblasts and osteoclasts, as well as altered osteo-adipogenic differentiation of bone marrow mesenchymal stem cells. The effect of alcohol on bone is regulated by Wnt and mTOR pathways. In addition, systemic changes such as hormone homeostasis, oxidative stress, but also altered parathyroid hormone (PTH) - vitamin D and growth hormone - insulin-like growth hormone (IGF) axes have indirect effects on bone cells. Long-term excessive alcohol consumption reduces the absorption of nutrients, testosterone synthesis and the ability of stem cells to differentiate into cells of the osteogenic lineage, which results in a decrease in the activity and level of osteoblastic differentiation while simultaneously increasing osteoclastogenesis. However, particularly controversial are the data of numerous studies that confirm that light to moderate alcohol consumption has a positive effect on bone structure, and that the primary mechanism leading to improvement in bone mineral density is suppression of bone resorption. What still remains unclear is the more precise determination of the amount and type of alcoholic drink that has a benefit on bones, and when toxicity begins to manifest itself, with a consequent decrease in bone mineral density. Therefore, it is necessary to carry out further tests in order to start therapy in a timely manner and prevent pathological bone fractures.